KINERJA KEUANGAN DAERAH KABUPATEN BADUNG DALAM PELAKSANAAN OTONOMI DAERAH - I Putu Santika; Ida Bagus Made Punia Adnyana (Journal of Applied Management Studies, 2022)
This study aims to determine the regional financial performance of Badung Regency in the implementation of regional autonomy. The study used secondary data obtained from the Regional Government Financial Reports of Badung Regency. Researchers conducted an analysis of financial performance with indicators of regional financial independence, efficiency and effectiveness in the 2015-2019 period. The results of the study found that 1) The level of financial independence of the Badung Regency area was classified as very good with a ratio value of 489.8 percent. 2) The level of the financial efficiency ratio of the Badung Regency Government is in the very effective criteria with an efficiency ratio value of 3.59 percent. During a period of five years the financial efficiency of the Badung Regency Government has increased in terms of the percentage ratio, although in 2019 it decreased by 1.62%, but based on the financial efficiency criteria, the Badung Regency Government is still in the very efficient criteria; and 3) The level of financial effectiveness of Badung Regency is in the effective criteria with an effectiveness ratio of 95 percent.